2007
DOI: 10.1007/s10592-007-9291-5
|View full text |Cite
|
Sign up to set email alerts
|

High gene flow in oceanic bottlenose dolphins (Tursiops truncatus) of the North Atlantic

Abstract: Despite the openness of the oceanic environment, limited dispersal and tight social structure often induce genetic structuring in marine organisms, even in large animals such as cetaceans. In the bottlenose dolphin, mitochondrial and nuclear DNA analyses have revealed the existence of genetic differentiation between pelagic (or offshore) and coastal (or nearshore) ecotypes in the western North Atlantic, as well as between coastal populations. Because previous studies concentrated on continental margins, we ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
80
3
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 63 publications
(102 citation statements)
references
References 52 publications
16
80
3
1
Order By: Relevance
“…In common dolphins of the North Atlantic, lack of population structure within the eastern and western basins suggested that individuals might undergo long-distance migration movements (Mirimin et al 2009). In the Azores, high levels of gene flow were found in bottlenose dolphins of the species T. truncatus (Quérouil et al 2007), and a photo-identification study revealed that some individuals travel between groups of islands and probably come from outside the archipelago ). In the eastern tropical Pacific, capture-recapture data showed that dolphins of the genus Stenella can travel more than 1000 km, and seasonal shifts in distributions suggested that movements could be as wide as 2500 km (Reilly 1990).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In common dolphins of the North Atlantic, lack of population structure within the eastern and western basins suggested that individuals might undergo long-distance migration movements (Mirimin et al 2009). In the Azores, high levels of gene flow were found in bottlenose dolphins of the species T. truncatus (Quérouil et al 2007), and a photo-identification study revealed that some individuals travel between groups of islands and probably come from outside the archipelago ). In the eastern tropical Pacific, capture-recapture data showed that dolphins of the genus Stenella can travel more than 1000 km, and seasonal shifts in distributions suggested that movements could be as wide as 2500 km (Reilly 1990).…”
Section: Resultsmentioning
confidence: 99%
“…Residency has been shown to be associated with population differentiation in other species (e.g., bottlenose dolphins of the species T. aduncus in Australia, Möller and Beheregaray 2004; spinner dolphins in the South Pacific, Oremus et al 2007). However, in the Azores, no population differentiation was found in T. truncatus despite the existence of known resident individuals (Quérouil et al 2007;Silva et al 2008). The extent of differentiation might depend on the proportion of individuals that are resident.…”
Section: Absence Of Population Structure Within and Between Archipelagosmentioning
confidence: 93%
See 2 more Smart Citations
“…However, it was not considered as a valid species of Tursiops by the Committee on Taxonomy of The Society for Marine Mammalogy (2016). Despite the broad geographic coverage of all these studies, bottlenose dolphins have mostly been studied in peri-continental and shallow waters, and very little is known about offshore populations (Klatsky et al, 2007;Quérouil et al, 2007;Baird et al, 2009).…”
Section: Introductionmentioning
confidence: 99%